Poltical trust and the success of fiscal consolidations - Dóra Győrffy (Transformation, Integration and Globalization Economic Research (TIGER), 2007)
The paper examines the effects of political trust on fiscal consolidations. Building on the works of Easton (1965) and Gamson (1968) a theoretical framework is derived on the main channels through which the success of fiscal consolidation can be affected by the level of political trust in the system. The predictions of the theory are tested quantitatively based on evidence from the Economic and Monetary Union and qualitatively through a most-likely - least-likely case comparison between Hungary and Sweden. The results provide strong support for the hypotheses and indicate that in the absence of external pressures lasting fiscal consolidations can take place only in a high-trust regime. In a low-trust regime even if an external crisis triggers adjustment, the incentive to buy support through short-term promises ultimately erodes the commitment to restraint and imbalances reemerge.
Keywords: 330; trust; fiscal consolidation; budgetary reforms; economic populism; role of ideas; Haushaltskonsolidierung; Finanzreform; Finanzpolitik; Vertrauen; Ungarn; Schweden; EU-Staaten